Is the Change of Soil Carbon Capacity Persistence Rising or Remain Stable With Maturity of Vegetation Restoration? - Liu, Qian; Wang, Peipei; Xue, Zhijing; Zhou, Zhengchao; Liu, Jun'e; An, Shaoshan (Frontiers in Soil Science, 2021)
Emerging consensus is that land-use change resulting through the “Grain for Green” project has had a significant impacted on soil organic carbon (SOC), thereby probably enhancing the carbon sequestration capacity of terrestrial ecosystems. However, it remains largely unknown whether a watershed acts as a source or sink of soil carbon during the later period of ecological restoration. This study comprehensively investigated the changes of SOC stock in 1987, 2005, 2010 and 2017 along different land-use types. It was aimed to evaluate the dynamics to SOC storage capacity over different vegetation restoration maturity in the Shanghuang Watershed, China. The results showed that restoration increased the accumulation of organic carbon pools in the early stage. Significant increases in SOC stock were observed in shrubland and grassland in comparison to that in other land uses, and these two land-use types represented the optimal combination for ecological restoration in the basin. The SOC stock did not increase indefinitely during the long-term vegetation restoration process, but rather first increased rapidly with vegetation planting and reached a peak at about 2010, following which it declined slightly. Therefore, pure vegetation restoration cannot maintain a permanent soil carbon sink, some measures to maintain the stability of carbon and to prolong soil C persistence are essential to take.